The Perceived Value, Consumer Consciousness, and Purchase Decisions: The Impact of Choice Overload in Indonesia’s Digital Marketplaces - Merna Rosalina; Yolanda Masnita; Kurniawati Kurniawati (Advances: Jurnal Ekonomi & Bisnis, 2026)
Purpose: This study examines the effects of quality consciousness, perceived value, fashion consciousness, brand consciousness, choice overload, and price consciousness on customer purchase decision-making, including their mediating effects, among male and female consumers shopping on digital marketplaces in Indonesia. Research Method: This study employed a quantitative research design. Data were collected from 300 respondents using non-probability purposive sampling. All valid responses were analyzed using Structural Equation Modeling (SEM) to test the relationships among the research variables. Results and Discussion: The findings indicate that quality consciousness positively affects perceived value. In addition, perceived value, fashion consciousness, brand consciousness, confusion due to overchoice, and price consciousness positively influence customer purchase decision-making. The study also confirms the mediating effects among the examined variables. The strongest relationship was found between quality consciousness and perceived value, indicating that consumers’ awareness of product quality plays an important role in shaping value perceptions and purchase decisions. Implications: Digital marketplace managers should emphasize product quality, especially for higher-priced products, to strengthen perceived value and encourage purchase decisions. Originality: This study contributes to consumer behavior research by integrating multiple consciousness-based factors and choice overload in explaining purchase decision-making in Indonesian digital marketplaces.